Chemical and Physical Assessment of Water Quality in the Panimbang River Estuary, Pandeglang, Indonesia - Feni Mustika Sari; Mochamad Fajar Deliaz; Akbar Rizqi Kurniawan; Yossy Ayuliansari; Riskia Chandra Widianti (Program Studi Kimia Universitas Negeri Jakarta, 2025)
The Panimbang River in Pandeglang, Indonesia, is widely used by residents for daily activities. This study analyzed water quality using physical parameters, including pH, temperature, dissolved oxygen (DO), Total Dissolved Solids (TDS), TSS (Total Suspended Solids), salinity, and alkalinity. Samples were taken around the estuary, which is surrounded by settlements. The results showed a pH of 4.50–6.49, below the standard of 6–9, indicating slightly acidic water. High temperatures, thought to be due to daytime sampling, affect DO. The average DO value was only 2.96 mg/L, well below the minimum threshold of 5 mg/L, indicating poor aeration. The average TDS is above 1000 ppm, indicating pollution from household waste and human activities. The average alkalinity of 384.976 mg/L CaCO₃ is within the safe range (30–500 mg/L), so it can stabilize pH. The water quality in the Panimbang River Estuary indicates environmental pressure from anthropogenic activities, resulting in slightly acidic water with low aeration and high solute content. However, adequate alkalinity still helps maintain the water's pH stability. This condition indicates the need for more intensive monitoring and waste management to protect estuarine ecosystems, which are vital to the community and the surrounding environment.